KSD model for plagiarism protection in hybrid pedagogy: the view of private college students - Chen, Lin; Abdullah, Nur Surayyah Madhubala; Saharuddin, Norzihani (Uzhhorod National University, 2024)
Relevance. Hybrid pedagogy has become the new norm of higher education due to the COVID-19 pandemic. However, there is still a problem of detecting plagiarism in hybrid pedagogy and the lack of methods to combat it, which makes it necessary to investigate this issue in more detail. Purpose. The purpose of the study is to reveal the views of students of Chinese private colleges on the knowledge, causes and methods of solving the problem of plagiarism and provide an effective model of protection against plagiarism. Methodology. To achieve this goal, the methods of analysis and synthesis, comparison, and generalization, as well as the questionnaire and interview methods were used. Results. The study found that hybrid pedagogy can contribute to plagiarism due to the lack of control over students and free access to Internet resources. A survey was conducted among students of Chinese private and public colleges, which showed greater awareness of plagiarism among students of public colleges. The results of a survey and interview of respondents were compared and determined that students of Chinese private colleges are more likely to violate academic integrity than students of public colleges. The results of the study show that private colleges have neither method of punishing plagiarism in student papers nor methods of combating it. To provide an effective model of protection against plagiarism, methods of monitoring academic integrity in higher education institutions in Asia, Europe, Africa, and the USA were compared. Conclusions. The study proposed and described the Knowledge-Support-Defence (KSD) model as a method of combating plagiarism in Chinese colleges. The results of the study can be used by the management of higher educational institutions to develop academic integrity among students and researchers, as well as by teachers to fairly evaluate student work.